1999
DOI: 10.1007/s002770050480
|View full text |Cite
|
Sign up to set email alerts
|

Splenic rupture in a patient with acute myeloid leukemia undergoing peripheral blood stem cell transplantation

Abstract: Splenic rupture is a rare but well-recognized complication of hematological malignancies. Here, we present the case of a 22-year-old woman with the diagnosis of acute myeloid leukemia who was undergoing peripheral blood stem cell transplantation. On day + 10 she developed a hypovolemic shock due to rupture of her spleen and went to emergency laparotomy. This is the first report of splenic rupture during peripheral blood stem cell transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 8 publications
0
21
0
Order By: Relevance
“…4,7,11 However, this does not explain the cause of rupture in healthy donors. A probable cause or risk factor of rupture is not apparent from studying a limited number of cases or from the data available.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…4,7,11 However, this does not explain the cause of rupture in healthy donors. A probable cause or risk factor of rupture is not apparent from studying a limited number of cases or from the data available.…”
Section: Discussionmentioning
confidence: 99%
“…16 The splenomegaly has been attributed to infiltration of the red pulp by granulocytes in some cases as well as the presence of extramedullary hematopoiesis in others. Although splenomegaly seems to be a common side effect, there are only occasional cases of splenic rupture reported and we have attempted to identify all cases of splenic rupture related to G-CSF/GM-CSF therapy reported in the English literature (Table 1) [2][3][4][5][6][7][8][9][10][11][12][13] with an additional case from our institution. Recently, a similar study was published by Nuamah et al, 12 but it does not include all published cases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in the other case splenic rupture occurred on the sixth day of administration of G-CSF (at 16 mcg/kg/day) without evidence of any underlying disorder of the spleen or of a coagulation abnormality or trauma. In addition, Kasper et al [41] have reported a patient with acute myeloid leukemia, in remission, undergoing autologous peripheral blood stem cell transplantation who developed splenic rupture while on G-CSF injections (at 5 mcg/kg/day) during the peritransplant period prior to hematopoietic recovery.…”
Section: Discussionmentioning
confidence: 99%